Developing Arabic Media Based on Brain-Based Learning: Improving Mufrodat in School - Jailani, Mohammad (Tadris: Jurnal Keguruan dan Ilmu Tarbiyah, 2021)
Education in the era of transformation affects the development of science and technology since teachers are directed to be innovative in language teaching. This study aimed to develop Arabic language media based on brain-based learning for SMK (Vocational High School) Muhammadiyah 3 Yogyakarta during the Covid-19 period. This study employed Research and Development (R and D)method with the development model proposed by Borg and Gall. The research subjects consisted of ten students and three teachers. Research data were collected through interviews, observation, and documentation techniques. The researchers implemented the data analysis technique by Miles and Huberman. Furthermore, the researchers ensure the data validity by triangulation. The analysis indicated that the Arabic language media was feasible to be used. The validity had been tested by two material experts and two media experts. Material expert 1 gave an average score of 4.27, and material expert 2 gave an average score of 4.81, both within the high category. On the other hand, media expert 1 gave an average score of 4.42, and media expert 2 gave an average score of 3.71, both within the high category. Also, the product had been tested on ten students during the small-scale trial and the large-scale trial. According to material experts' validation, the weakness of the product was related to the title of the material and the duration. Therefore, the developed media could increase mufrodat mastery in the industrial 4.0 era.